Exosomal lncRNA-p21 levels may help to distinguish prostate cancer from benign disease - Işın, Mustafa; Uysaler, Ege; Özgür, Emre; Köseoğlu, Hikmet; Şanlı, Öner; Yücel, Ömer B.; Gezer, Uğur; Dalay, Nejat (Frontiers in Genetics, 2015)
Exosomes are membranous vesicles containing various biomolecules including lncRNAs which are involved in cellular communication and are secreted from many cells including cancer cells. In our study, investigated the exosomal GAS5 and lincRNA-p21 lncRNA levels in urine samples from 30 patients with prostate cancer (PCa) and 49 patients with benign prostatic hyperplasia. Quantification of lncRNA molecules was performed by real-time PCR. We observed a significant difference in the exosomal lincRNA-p21 levels between PCa and BPH patients whereas the GAS5 levels did not reveal a difference. Our data suggest that the discriminative potential of exosomal lincRNA-p21 levels may help to improve the diagnostic prediction of the malignant state for patients with prostate cancer.